Answer :

(B ∩ C) = {x:x ϵ B and x ϵ C}

= {5, 6}

(A – (B ∩ C)) =

A–(B ∩ C) is defined as {x ϵ A : x ∉(B ∩ C)}

A = {1, 2, 4, 5}

(B ∩ C) = {5, 6}

(A – (B ∩ C)) = {1, 2, 4}

R.H.S:

(A – B) =

A–B is defined as {x ϵ A : x ∉ B}

A = {1, 2, 4, 5}

B = {2, 3, 5, 6}

A–B = {1, 4}

(A–C) =

A–C is defined as {x ϵ A : x ∉ C}

A = {1, 2, 4, 5}

C = {4, 5, 6, 7}

A–C = {1, 2}

(A – B) ∪ (A–C) = {x:x ϵ (A – B) OR x ϵ (A – C) }.

= {1, 2, 4}

Hence verified.

Rate this question :

Let A = {a, b, c,RS Aggarwal - Mathematics

If A and B be twoRS Aggarwal - Mathematics

(i) If A <span laRS Aggarwal - Mathematics

Using propeMathematics - Exemplar

If A and B are twRS Aggarwal - Mathematics

In a town of 10,0RS Aggarwal - Mathematics

If A and B are twRS Aggarwal - Mathematics

If <a name="MTBlaRS Aggarwal - Mathematics

If n(A) = 3 and nRS Aggarwal - Mathematics

For any sets A, BRS Aggarwal - Mathematics